PENGARUH ORGANISASI PERDAGANGAN DUNIA (WTO) PADA REGULASI HUKUM BISNIS PARIWISATA DI INDONESIA - Ni Made Trisna Dewi; Agus Surya Manika; A.A. Mas Adi Trinaya Dewi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
Adjustment of statutory regulations in the field of tourism business law in Indonesia is one of the consequences of the WTO agreement, thus the GATS-WTO agreement does not only concern Law Number 10 of 2009 concerning Tourism, but also all other related regulations. with tourism, such as labor regulations, Intellectual Property regulated in TRIP's, investment regulations (TRIM's), etc. These regulations will be affected by the provisions of the GATS-WTO, which must immediately be adjusted and harmonized with the GATS agreement commitment that has been agreed by Indonesia. It is by putting the principles of liberalization that it can have an impact on tourism arrangements in Indonesia which are not liberal but adhere to the principles of the Pancasila democracy state. The impact of the WTO on Indonesia's tourism business law arrangements related to TRIMS and GATS is the creation of tourism regulations that can protect local communities and cultures, limiting the liberalization of foreign investors from modern countries. The tourism arrangement must be in accordance with the nature of the purpose of its existence, namely to: increase economic growth; improve people's welfare; eradicating poverty; overcoming unemployment; preserving nature, environment and resources; promote culture; lifting the image of the nation; cultivate a love of the country; strengthen national identity and unity; and strengthen friendship between nations.